Feature activation during word recognition: action, visual, and associative-semantic priming effects - Lam, Kevin J. Y.; Dijkstra, Ton; Rueschemeyer, Shirley-Ann (Frontiers in Psychology, 2015)
Embodied theories of language postulate that language meaning is stored in modality-specific brain areas generally involved in perception and action in the real world. However, the temporal dynamics of the interaction between modality-specific information and lexical-semantic processing remain unclear. We investigated the relative timing at which two types of modality-specific information (action-based and visual-form information) contribute to lexical-semantic comprehension. To this end, we applied a behavioral priming paradigm in which prime and target words were related with respect to (1) action features, (2) visual features, or (3) semantically associative information. Using a Go/No-Go lexical decision task, priming effects were measured across four different inter-stimulus intervals (ISI = 100 ms, 250 ms, 400 ms, and 1,000 ms) to determine the relative time course of the different features . Notably, action priming effects were found in ISIs of 100 ms, 250 ms, and 1,000 ms whereas a visual priming effect was seen only in the ISI of 1,000 ms. Importantly, our data suggest that features follow different time courses of activation during word recognition. In this regard, feature activation is dynamic, measurable in specific time windows but not in others. Thus the current study (1) demonstrates how multiple ISIs can be used within an experiment to help chart the time course of feature activation and (2) provides new evidence for embodied theories of language.